ANALISIS KESEDIAAN KONSUMEN UNTUK MEMBAYAR PRODUK TEMPE HYGIENE RUMAH KEDELAI GROBOGAN DI KABUPATEN GROBOGAN - Desita Kencana Sari; Titik Ekowati; Agus Setiadi (University of Jember, 2020)
Public awareness of health is currently rising. Now consumers tends to consider the health benefits such as tempe hygiene. Tempe hygiene processed with hygienic using Varieties Grobogan non-GMO, therefore it has good quality and higher price. This study aims to describe the characterictics of consumers, analyze the average value of the maximum that consumers are willingness to pay and determine the factors that influence consumers’ willingness to pay. This study was conducted at 5 Tempe Hygiene market place in Grobogan with a hundred respondents selected using a quota sampling method. Data were analyzed using the descriptive analysis to describe consumer characteristics, CVM (contingent valuation methode) analysis to calculate the average value of maximum WTP and logistic regression analysis to analyze the factor that affects the value of WTP. The result showed that as many as 82% of respondents were willing to pay more for tempe hygiene. The value of WTP is Rp 6,432.00 per pack (350 gram). Factors that significantly affect consumers’ WTP values were age, income and product quality. Based on the analysis result, it can be concluded that the consumers were willing to pay more for tempe hygiene products with the difference between the average price and the real price of 7,19%.